Keterampilan Kerja Punk Jalanan dalam Meningkatkan Adversity Quotient - A’izza Wardatul Hamro Al Rozi; Almisar Hamid (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Every individual certainly has the ability to face and overcome difficulties in life, so that it does not have a profound negative impact on the business they are undertaking in their lives, as is also the phenomenon experienced by street punks. Street punks need various work skills activities that can minimize problems in the socio-economic conditions they experience, so that they do not result in setbacks and are expected to function fully in carrying out life activities. Various job skills activities that can increase the Adversity Quotient are carried out by the street punk community in South Tangerang. The aim of this research is to determine the work skills process of street punks based on the LEAD method in determining the AQ level of street punks at the level of quitters, campers, or climbers. This research uses descriptive qualitative methods by collecting data through interviews and documentation. The research results concluded that street punks’ work skills were carried out by being guided by both individuals and groups which resulted in an increase in street punks’ AQ. However, there are still obstacles in the process due to age, environmental, economic and indiscipline factors.